KAWASAN PEMUKIMAN VETERAN MAKASSAR PENEKANAN ARSITEKTUR KOLONIAL - SM, Nurul Fadhilah; Wasilah, Wasilah (Nature : National Academic Journal of Architecture, 2015)
Veteran 45 is a former fighter of the Republic of Indonesia in his youth struggling with body and soul in order to maintain the independence of Indonesia . They are witness to the passage of a long history of Indonesia today , but the lack of attention the government makes almost no trace of them . This paper attempts to realize the region that brings together all the activities of veterans into a residential area with an emphasis Dutch colonial architecture as well as a symbol of appreciation to the members of veterans in Makassar based with elements of urban design.